ECONOMIC-MATHEMATICAL MODELING FLEXIBILITY AND PRODUCTIVITY RATIOS IN THE FORMATION OF A SYSTEM OF INTERNAL LOGISTICS OF HIGH-TECH ENTERPRISES - V. Baranov (Модернизация, инновация, развитие, 2016)
The article describes the features of construction of the system internal logistics of high-tech enterprises. It describes a range of problems solved by these systems. As part of the internal logistics system is considered one of the tasks of operational and production management calendar. Considered in the article the problem associated with the formation of the production program of diversified production. As part of this task is received economic and mathematical model that establishes the relation between the parameters of fl exibility and performance to organizational and production structure of the high-tech enterprises.